Effects of Gamma Irradiated and Non-Irradiated Sewage Sludge on Essential Oil Content and Constituents of Ocimum basilicum L. - B Asgari Lajayer; NA Najafi; E Moghiseh; M Mosaferi; J Hadian (Institue of Medicinal Plants, ACECR, 2019)
Background: The increasing amount of sewage sludge (SS) and more legislative regulation of its disposal have stimulated the need for developing new technologies including gamma irradiation to recycle SS efficiently. Objective: To evaluate the effects of gamma irradiated and non-irradiated SS (SSGI and SSNI, respectively) on essential oil (EO) content and composition of Ocimum basilicum L. Methods: A greenhouse experiment was conducted with 15, 30, and 60 g kg-1 of SS irradiated with absorbed doses of 5, 10, and 20 kGy gamma-ray and soil without SS and irradiation as the control treatment. The essential oil was isolated by hydro-distillation and analyzed by Gas chromatography and Gas chromatography-mass spectrometry techniques. Results: The applications of SSGI and SSNI at all levels except 15 g kg-1 significantly enhanced EO content compared to the control. The using of 60 g kg-1 SS in each absorbed dose significantly reduced EO yield relative to the control, while it was significantly increased under 15 and 30 g kg-1 SSNI and SSGI. Also, in 60 g SS kg-1, the restriction effects on EO yield were mitigated with increasing the absorbed dose of gamma-ray, but it was insignificant with increasing absorbed dose to 10 and 20 relative to 5 kGy. The methyl chavicol as a major constituent of EO was significantly increased in SSGI and SSNI as compared with the control. However, the increment in the methyl chavicol content was not significant between the treatments ≥ 30 g kg-1 SSGI or SSNI and 15 g kg-1 SS at absorbed dose of ≥10 kGy. 98 Conclusion: To improve essential oil content and composition, application of ≤ 30 g kg-1 sewage sludge with 5 kGy absorbed dose of gamma-ray can be suggested at similar conditions.